Equity issues and offering dilution - Asquith, Paul; Mullins, David W. (Journal of Financial Economics, 1986)
This study investigates the effect on stock prices of seasoned equity offerings. The results demonstrate that the announcement of equity offerings reduces stock prices significantly. For industrial issues, regression results indicate that announcement day price reduction is significantly and negatively related to the size of the equity offering. The results appear not to be explained by changes in capital structure associated with the equity offerings. The findings are consistent both with the hypothesis that equity issues are viewed by investors as negative signals and with the hypothesis that there is a downward sloping demand for a firm's shares.